Friction reduction and viscosity modification of cellulose nanocrystals as biolubricant additives in polyalphaolefin oil. (15th September 2019) - Li, Ke; Zhang, Xiao; Du, Chen; Yang, Jinwan; Wu, Bolang; Guo, Zhiwei; Dong, Conglin; Lin, Ning; Yuan, Chengqing
Graphical abstract: Highlights: Cellulose nanocrystal is added into polyalphaolefin base oil as lubricant additive. CNC is modified by stearoyl chains to improve its compatibility with PAO oil. The viscosity of hybrid oil is modified due to the chains entanglement. The friction and wear of hybrid oil are reduced from CNC mending effect. Abstract: With the increasing requirement of environmental protection, the development of lubricating materials with non-toxicity and good biodegradability becomes more and more significant. As the novel green nanomaterial derived from natural cellulose, cellulose nanocrystals (CNCs) in the present work were prepared from native cotton and added into polyalphaolefin (PAO) base oil as the lubricant additive. To improve the compatibility of CNCs with PAO, the surface of CNCs were grafted by stearoyl chains, which entangled with polyolefin chains and led to a good dispersibility and stability of the colloidal solution. This hybrid oil with the elevated viscosity improved the formation of lubricant film in the boundary lubrication regime. Combining with the mending effect of CNC particles on the surface roughness and scars, both the friction and the wear were dramatically reduced. Specifically, the introduction of 2 wt% modified nanocrystals (mCNC) in PAO base oil reduced the coefficient of friction (COF) by 30%. The results of this study suggest that cellulose nanocrystal is a promising ecofriendly and effective lubricant additive.